THE CORRELATION BETWEEN STUDENTS’ PERSONALITY TYPES (EXTROVERT AND INTROVERT) AND READING COMPREHENSION: A STUDY IN SMPN 2 LIRIK - Riza Astriani; Yuli Tiarina (University of Kuningan, 2025)
Reading is one of the important basic skills in English. Personality types also have a relationship with students' reading comprehension. There are many ways of classifying one’s personality. One of these is categorizing them into extrovert or introverted types. This research was conducted through quantitative non-experimental research. The population of this research was all IX class students at SMPN 2 Lirik. The study used Eysenck’s Personality Questionnaire to measure students’ personality types and examined their correlation with reading comprehension. While no significant overall correlation was found, extrovert and introvert characteristics influenced specific comprehension processes differently. Based on the data that has been collected, the level of students' extrovert personality, the results showed that the overall average score is 38.38. This places most students in the medium extrovert personality category. Meanwhile, regarding the level of students' introverted personality, the results showed that most students were in the medium category, with an average overall score of 42.17 from a total of 65 respondents. Both extroverts and introverts have a significant role in their reading comprehension abilities. Although overall there was no significant correlation between personality type (X) and reading comprehension based on the t-count value of 0.227 which is lower than the t-table of 1.998 and a significance value of 0.821 (greater than α = 0.05), the findings from the analysis of each indicator indicate that extrovert and introvert personality characteristics have different influences on the process of understanding texts. Keywords: Students’ personality types (extrovert and introvert), reading comprehension